DEVOTING MEDIA PLURALISM THROUGH ACHIEVING CULTURAL DIVERSITY IN DIGITAL MEDIA: : (Features, Constituents And Obstacles ) - ghezal, abderrazzek; bourahli, wafa (ALBAHITH ALALAMI, 2019)
The media of all kinds have the task of introducing, expressing and objectively representing the cultures of different societies in various types and forms of press and media. The precept of media pluralism is the basis for freedom of expression & the cornerstone of its realization. Therefore, it is linked to the establishment of several conditions and elements in order to establish it as a principle and practice. Issues of cultural diversity in media and cultural pluralism are one of the most important elements and indicators. So, this paper aims to shed light on the concept of media pluralism and related concepts within the framework of cultural diversity and multicultural indicators. Thus, highlighting the features of cultural diversity in digital media and its roles in promoting it in light of the characteristics and transformations that have touched many aspects of human life.